Circular Degree Choosability - Norine, Serguei; Zhu, Xuding (The Electronic Journal of Combinatorics, 2008)
We extend a characterization of degree-choosable graphs due to Borodin, and Erdős, Rubin and Taylor, to circular list-colorings.